Ergenlerde farkındalık, psikolojik iyi oluş, sosyal medya kullanımı ve internet kullanım süresi: bir yapısal eşitlik modellemesi - Evli, Mahmut; Albayrak, Eda; Şimşek, Nuray; Uzdil, Nurcan (Journal of Dependence, 2023)
Objective: Psychological well-being is a concept associated with mindfulness and the use of social media. Limited information is available in the literature on the nature of this relationship and the underlying intermediary mechanisms. We also aimed to determine the mediator role of social media use and time spent online in the association between mindfulness and psychological well-being. Method: This study included 429 teenagers. Data was collected through introductory information form, social media use scale, psychological well-being scale, and mindful attention awareness scale. Structural equation modeling method was used in the analysis of the data. Results: A significant positive correlation was found between mindfulness and psychological well-being, and a significant negative correlation was found between mindfulness and time spent online. Social media use did not play a mediator’s role in the correlation between mindfulness and psychological well-being, while the daily time spent online played a mediator’s role. Conclusion: As mindfulness increases in adolescents, psychological well-being increases and the time spent on the internet decreases. While the use of social media does not have a mediating role in the relationship between mindfulness and psychological well-being, the time spent on the internet has a mediating effect. Future research should be conducted with different groups and variables on the impact of social media use on psychological well-being and mindfulness.